Preventing Smoking in Children: Implementation Non-Smoking Area in Palu City - Napirah, Muhammad Ryman; Vidyanto, Vidyanto; Hasanah, Hasanah (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
The prevalence of smokers in Palu City aged <20 years experienced fluctuations, namely in 2015 there were 153 smokers, in 2016 there were 315 smokers, in 2017 there were 1,073 smokers and in 2018 969 were smokers. The purpose of this study was to determine the concepts of communication, resources, disposition, and bureaucratic structure in the implementation of KTR policies in preventing smoking habits in children at the Palu City Health Office. This type of research was qualitative with triangulation techniques. The number of informants used is 3 people. Data analysis used an analysis approach (content analysis) with matrix techniques. Matrix analysis showed that the bureaucratic structure had been running well in its implementation to prevent smoking habits in children, namely by implementing KTR policies that were by the SOP. While the variables of communication, disposition, and resources had not been good in its implementation to prevent smoking habits in children at the Palu City Health Office due to differences of opinion among policymakers, lack of human resources, and lack of commitment from stakeholders in implementing KTR policies. It is expected that policymakers, especially the Health Office of Palu City to evaluate by reviewing the aspects of communication, resources, disposition, and bureaucratic structure as input feedback to minimize the problems obtained related to the implementation of KTR policies so that all indicators in implementing policies can be implemented properly.